When theory and practice clash: participatory governance and management in Takht-e Soleyman. Issue 2 (15th May 2017) - Donato, Fabio; Lohrasbi, Anahita
Abstract : Purpose: Cultural landscapes are no more considered only as territories of cultural interest but also as integrated systems of cultural, social, and economic values. The adjustment of this consideration with the modern paradigms of collective governance and management necessitates investigations on challenges of management of cultural landscapes for valorizing their resources toward sustainable development. In this framework, the purpose of this paper is to analyze the state of participatory governance and management in cultural landscapes, focusing on the case of Takht-e Soleyman World Heritage Site (WHS) in Iran. Design/methodology/approach: The paper presents the results of a study based on a theoretical analysis, accompanied by in-depth interviews with the key actors in the cultural heritage governance and management sectors, and large-scale surveys of the local population through the circulation of questionnaires. Findings: This paper debates the reasons behind and the way forward to make governance and management approaches consistent with international theories and national policies. The analysis focuses on rural cultural landscapes and accordingly the Takht-e Soleyman WHS is deeply investigated. Originality/value: The policies for participatory governance and management of rural cultural landscapes have been raised in the literature. However, more attention has to be paid to the strategies and mechanisms based on local features for their implementation. The study detailed in this paper makes a contribution to the debate on the design and implementation of participatory governance and management systems in this field by examining the actual extent of successful implementation of theoretical values and national policies in the case of Takht-e Soleyman WHS.